Evaluation of two electronic-rehabilitation programmes for persistent knee pain: protocol for a randomised feasibility trial - Philip G Conaghan; Kim L Bennell; Mark Conner; Rana S Hinman; Sarah R Kingsbury; Elizabeth M A Hensor; Gretl A McHugh; Christine Comer; Dawn Groves-Williams; Rachel K Nelligan (BMJ Open)
Introduction Persistent, knee pain is a common cause of disability. Education and exercise treatment are advocated in all clinical guidelines; however, the increasing prevalence of persistent knee pain presents challenges for health services regarding appropriate and scalable delivery of these treatments. Digital technologies may help address this, and this trial will evaluate the feasibility and acceptability of two electronic-rehabilitation interventions: ‘My Knee UK’ and ‘Group E-Rehab’.Methods and analysis This protocol describes a non-blinded, randomised feasibility trial with three parallel groups. The trial aims to recruit 90 participants (45 years or older) with a history of persistent knee pain consistent with a clinical diagnosis of knee osteoarthritis. Participants will be randomly assigned in a 1:1:1 allocation ratio. The ‘My Knee UK’ intervention arm will receive a self-directed unsupervised internet-based home exercise programme plus short message service support (targeting exercise behaviour change) for 12 weeks; the ‘Group E-Rehab’ intervention arm will receive group-based physiotherapist-prescribed home exercises delivered via videoconferencing accompanied by internet-interactive educational sessions for 12 weeks; the control arm will receive usual physiotherapy care or continue with their usual self-management (depending on their recruitment path). Feasibility variables, patient-reported outcomes and clinical findings measured at baseline, 3 and 9 months will be assessed and integrated with qualitative interview data from a subset of Group E-Rehab and My Knee UK participants. If considered feasible and acceptable, a definitive randomised controlled trial can be conducted to investigate the clinical effectiveness and cost-effectiveness of one or both interventions with a view to implementation in routine care.Ethics and dissemination The trial was approved by the West of Scotland Research Ethics Committee 5 (Reference: 20/WS/0006). The results of the study will be disseminated to study participants, the study grant funder and will be submitted for publication in peer-reviewed journals.Trial registration number ISRCTN15564385.